2021
DOI: 10.1017/gov.2021.4
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of the Legitimacy of Citizens’ Assemblies in Deeply Divided Places? Evidence of Public and Elite Opinion from Consociational Northern Ireland

Abstract: How much public and elite support is there for the use of a citizens’ assembly – a random selection of citizens brought together to consider a policy issue – to tackle major, deadlock-inducing disagreements in deeply divided places with consociational political institutions? We focus on Northern Ireland and use evidence from a cross-sectional attitude survey, a survey-based experiment and elite interviews. We find that the general public support decision-making by a citizens’ assembly, even when the decision r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Members of the opposition may exaggerate their hostility towards sortition. Hence, anonymous interviews might be a useful complement to our analysis (see Niessen, 2019;Rangoni et al, 2021;Garry et al, 2021). Another limitation of our study is the lack of quantitative insight.…”
Section: Discussion: Some Lessons From the French Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Members of the opposition may exaggerate their hostility towards sortition. Hence, anonymous interviews might be a useful complement to our analysis (see Niessen, 2019;Rangoni et al, 2021;Garry et al, 2021). Another limitation of our study is the lack of quantitative insight.…”
Section: Discussion: Some Lessons From the French Experiencementioning
confidence: 99%
“…Recent empirical evidence provides preliminary support to the hypothesis of a legitimacy conflict: elitist MPs who see themselves as more competent than ordinary citizens tend to consider that all democratic legitimacy emanates from elections, are particularly critical about deliberative mini-publics and reject the very idea of representation through sortition (Rangoni, Bedock, & Talukder, 2021), especially when it goes beyond consultation (Niessen, 2019;Garry et al, 2021). In this article, we look for further evidence of a legitimacy conflict in practice.…”
Section: Two Potentially Competing Forms Of Representationmentioning
confidence: 94%
“…As above, it is unionism's potential self-exclusion from this kind of deliberative forum that has dominated the debate on the appropriateness of citizens' assemblies for dealing with the constitutional question in the region (see Flynn, 2021). Moreover, it has been suggested that without unionist inclusion, the process could not be viewed as legitimate (see Flynn, 2021; see Garry et al, 2021Garry et al, , 2022, for discussions of potential models). Disputes around whether unionists would participate in a citizens' assembly on the constitutional question are likely to continue, but it is also important to examine the potential effects of this mechanism on other social groups; an issue currently buried under the machinations of on-going ethno-nationalist inspired quarrels.…”
Section: Citizens' Assemblies and Gender Justicementioning
confidence: 99%
“…Arguably, it is the views, and indeed behaviour, of these polarized citizens that constitute the toughest test for democratic decision-making in general. Moreover, the few to study minipublics in a polarized setting often do so without examining the effect of different forms and individuals' degree of polarization (Garry et al, 2022;Pow, 2021). Consequently, we lack insights into how minipublics are perceived by highly polarized citizens, and to what extent these perceptions differ for more moderate citizens.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they have focused on polarizing issues rather than polarized citizenssimilar to the few empirical studies that examine perceived minipublic legitimacy on a divisive issue such as migration (Pilet et al, 2022;Werner and Marien, 2022). Meanwhile, the few studies that look at minipublics in a highly polarized context do not look at the impact of different forms of polarization on perceived minipublic legitimacy (Garry et al, 2022;Pow, 2021). All in all, we lack insights into the perceived legitimacy of minipublics among polarized citizens and how these perceptions differ from those held by more moderate citizens.…”
mentioning
confidence: 99%